PERSEPSI MAHASISWA PGSD UNIVERSITAS NUSANTARA PGRI KEDIRI TERHADAP PERKULIAHAN DARING SELAMA MASA PANDEMI - Zunaidah, Farida Nurlaila (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of this research was to knowing the perceptions of Prodi PGSD subject Universitas Nusantara PGRI Kediri about online lectures during the pandemic. This perception is related to students 'knowledge of online lectures, students' feelings when they first took online lectures, various online media used to support online lectures and the most effective online media obtained and assisted in online lectures. This research method uses descriptive qualitative which is processing data from the survey results using Google forms. Based on survey data, it is known that 69.1% of students quite understand the concept of online lectures, 62.4% of students feel confused when they first do online lectures, 78.9% of students choose WhatsApp Group as a online lectures media and 75.9% of students consider WhatsApp Group is very easy and effective to use in supporting online lectures.